Back-to-basics: Fever is a syndrome and not just pyrexia - Lucien Wasingya-Kasereka; John Kellett (South Sudan Medical Journal, 2022)
Fever is a common presenting complaint in sub-Saharan Africa. Although it has many causes, the symptoms of fever, with or without an elevated body temperature, should always make the clinician suspect infection. The other presentations associated with fever often help identify its likely cause. However, the features of fever that make it life-threatening continue to bedevil physicians.